Comparison of the Characteristics of Cytokine Storm and Immune Response Induced by SARS-CoV, MERS-CoV, and SARS-CoV-2 Infections - Liu T (Dove Medical Press, 2021)
Tong Liu,1,* Meng Feng,2,* Zexin Wen,3 Yijie He,1 Wei Lin,2 Min Zhang1 1Department of Medicine, Xizang Minzu University, Xianyang, Shaanxi, People’s Republic of China; 2School of Basic Medicine, Shandong First Medical University & Shandong Academy of Medical Sciences, Jinan, Shandong, People’s Republic of China; 3Department of Clinical Medicine, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min ZhangDepartment of Medicine, Xizang Minzu University, Xianyang, People’s Republic of ChinaTel +86 2918681997994Email zhangmin-wen@163.comWei LinSchool of Basic Medicine, Shandong First Medical University & Shandong Academy of Medical Sciences, Jinan, People’s Republic of ChinaTel +86 53115098926353Email linw1978@163.comAbstract: Cytokine storm (CS) is a significant cause of death in patients with severe coronavirus pneumonia. Excessive immune–inflammatory reaction, many inflammatory cell infiltration, and extreme increase of proinflammatory cytokines and chemokines lead to acute lung injury and acute respiratory distress syndrome (ARDS). This review compares the characters of cytokine storms and immune responses caused by three highly pathogenic and infectious coronaviruses (HCoVs), including severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome-coronavirus (MERS-CoV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and analyzes the possible mechanisms to guide clinical treatment in the future.Keywords: cytokines, coronavirus pneumonia, cytokine storm, immune evasion, interferon